2020
DOI: 10.1037/rep0000304
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and outcomes in caregivers of persons with traumatic brain injury (TBI).

Abstract: Purpose/Objective: Spiritual well-being has been associated with better quality of life outcomes in caregivers, but the associations among the care recipient's functional status, the caregiver's spiritual well-being, and the caregiver's health-related quality of life (HRQOL) is unknown. Research Method/ Design: The study examined the Spiritual Well-Being Scale in caregivers of persons with traumatic brain injury (TBI; n ϭ 335). Participants completed measures from the Patient-Reported Outcomes Measurement Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…A espiritualidade se associa com melhores resultados de saúde mental e qualidade de vida dos cuidadores, e quanto maior a espiritualidade, melhor é a qualidade de vida. (26) Foi observado que cuidadores com uma pontuação alta no aspecto espiritual, apesar de expostos a altos níveis de estresse, sofrem um impacto psicológico em menor proporção, o que corrobora a hipótese que descreve como a espiritualidade ameniza o estresse, a angústia e a ansiedade experimentada (27) pelos cuidadores.…”
Section: Discussionunclassified
“…A espiritualidade se associa com melhores resultados de saúde mental e qualidade de vida dos cuidadores, e quanto maior a espiritualidade, melhor é a qualidade de vida. (26) Foi observado que cuidadores com uma pontuação alta no aspecto espiritual, apesar de expostos a altos níveis de estresse, sofrem um impacto psicológico em menor proporção, o que corrobora a hipótese que descreve como a espiritualidade ameniza o estresse, a angústia e a ansiedade experimentada (27) pelos cuidadores.…”
Section: Discussionunclassified
“…They found a significant correlation between positive religious coping and caregivers’ psychological wellbeing. The positive effect of religiosity has been described both in the caregivers of stroke survivors [ 38 ] and in victims of TBI [ 39 ]. Therefore, believing in a superior entity as well as a high frequency of religious commitment may be considered an important factor protecting against marital instability in couples with ABI spouses.…”
Section: Discussionmentioning
confidence: 99%
“…Affiliation to a religious community could help patients suffering from severe brain injury to develop increased religious beliefs. In addition, studies found that spirituality was a predictor for life satisfaction, distress and functional recovery in patients following a traumatic brain injury 64 and for caregivers’ outcomes 65 .…”
Section: Discussionmentioning
confidence: 99%